A study to evaluate the effect of nutritional intervention measures on admitted children in selected nutrition rehabilitation centers of Indore and Ujjain divisions of the state of Madhya Pradesh (India) - Gunjan Taneja; Sanjay Dixit; A K Khatri; Veena Yesikar; Deepa Raghunath; Sanjay Chourasiya (Wolters Kluwer Medknow Publications, 2012)
Backgound: The state of Madhya Pradesh has 1.3 million severely malnourished children. Nutrition rehabilitation centers (NRCs) were started in the state to control severe malnutrition and decrease the prevalence of severe malnourished children to less than 1% among children aged 1-5 years. Materials and Methods: The present study was conducted from November 2008 to October 2009; 100 children admitted to seven different NRCs in Indore and Ujjain divisions of Madhya Pradesh were observed during their stay at NRCs and the follow-up period to analyze the effect of interventional measures on select anthropometric indicators. Mothers of the children were interviewed on health issues and therapeutic feeding practices at the NRCs using a predesigned and pretested interview schedule. Results: The study group consisted of 48 boys and 52 girls; 60% were between 13 and 36 months of age. 93 children were analyzed for anthropometric indicators following a dropout rate of 7%. A statistically significant difference was obtained between the weight of children at admission and discharge (t=14.552, P<0.001); difference of mid upper arm circumference (MUAC) at admission and discharge was statistically significant (t=9.548, P<0.001). The average weight gain during the stay at the centers was 9.25 ± 5.89 g/kg/day. Though the number of severe malnourished children decreased from 85 to 43 following the stay at NRCs (χ2 = 44.195, P<0.001); 48.78% of the children lost weight within 15 days of discharge from the NRCs. Dropout rates of 9.89%, 23.07%, 42.65%, and 61.76% for the study group were obtained during the follow-up period of 6 months for the four follow-up visits conducted 15 days, 1, 3, and 6 months after discharge. The mothers of the children lacked adequate information on health issues and composition and preparation of therapeutic diets at the centers. Conclusion: The NRCs were effective in improving the condition of admitted children, but the effects were not sustained following discharge due to high drop-out rate and lack of adequate parental awareness. There is an urgent need to link these centers with community-based models for follow-up and improve health education measures to maintain the gains achieved.